2012
DOI: 10.1021/es301912q
|View full text |Cite
|
Sign up to set email alerts
|

Organic Micropollutants in Rivers Downstream of the Megacity Beijing: Sources and Mass Fluxes in a Large-Scale Wastewater Irrigation System

Abstract: The Haihe River System (HRS) drains the Chinese megacities Beijing and Tianjin, forming a large-scale irrigation system severely impacted by wastewater-borne pollution. The origin, temporal magnitudes, and annual mass fluxes of a wide range of pharmaceuticals, household chemicals, and pesticides were investigated in the HRS, which drains 70% of the wastewater discharged by 20 million people living in Beijing. Based on Chinese consumption statistics and our initial screening for 268 micropollutants using high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
82
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 49 publications
(87 reference statements)
8
82
0
1
Order By: Relevance
“…High dilution and fast metabolism of these compounds in the environment may explain the lower concentrations observed in surface water. All other pharmaceutical active compounds observed in this study have already been reported either in surface waters or in the influent/effluent of wastewater treatment plants in China (Bu et al 2013;Heeb et al 2012;Liu and Wong 2013;Qi et al 2014). Values for carbamazepine and diclofenac which were determined in this study with higher mean abundance have been reported in surface water in China with concentration ranges from nondetection to 675 and nondetection to 843 ng L −1 , respectively (Bu et al 2013).…”
Section: Analysis Of Pharmaceuticals and Polar Herbicidessupporting
confidence: 68%
See 3 more Smart Citations
“…High dilution and fast metabolism of these compounds in the environment may explain the lower concentrations observed in surface water. All other pharmaceutical active compounds observed in this study have already been reported either in surface waters or in the influent/effluent of wastewater treatment plants in China (Bu et al 2013;Heeb et al 2012;Liu and Wong 2013;Qi et al 2014). Values for carbamazepine and diclofenac which were determined in this study with higher mean abundance have been reported in surface water in China with concentration ranges from nondetection to 675 and nondetection to 843 ng L −1 , respectively (Bu et al 2013).…”
Section: Analysis Of Pharmaceuticals and Polar Herbicidessupporting
confidence: 68%
“…Regarding atrazine, seasonal fluctuations in concentration could be observed downstream of Beijing originating from agricultural areas. A distinct peak in atrazine level was observed in July 2009, whereas the levels in winter were near the LOQ which is an expected pattern for agricultural appliance of the pesticide (Heeb et al 2012). Our sampling campaign near the TGD in a more rural area of Hubei Province took place in September 2013 after the period Heeb et al observed the peak level of atrazine.…”
Section: Analysis Of Pharmaceuticals and Polar Herbicidesmentioning
confidence: 74%
See 2 more Smart Citations
“…The analytical method we used for applying 44 ISs for quantification has been reported elsewhere (Singer et al, 2010;Heeb et al, 2012). For targets where no structurally identical ISs were available, the ISs with the most similar retention times were used for quantification.…”
Section: Analysis Of Pesticides Pharmaceuticals and Household Chemimentioning
confidence: 99%